The Effect of Problem Based Learning Models in Online Learning Settings on Student Cognitive Learning Outcomes in History Subjects - Loppies, Megiridha; Badrujaman, Aip; Sarkadi, Sarkadi (LPPM Undiksha, 2021)
This study aims to examine the effect of problem-based learning models on the achievement of student learning outcomes in History subjects. This research was conducted at Pusaka 1 Jakarta Senior High School. The method used in this research is quantitative quasi-experimental with a nonequivalent control group design model. The population in this study were all students of class XI IPS as many as four classes at SMAS Pusaka 1 Jakarta. The research sample was determined by purposive sampling technique to determine one class as an experimental class using a problem-based learning model and another class as a control class using conventional learning models. The results of hypothesis testing using the t test, obtained tcount = 9.25,> from ttable = 1.99. Thus, Ho is rejected and Ha is accepted, so it can be concluded that there is a significant influence between problem-based learning models in online learning settings on cognitive learning outcomes of class XI IPS at SMAS Pusaka 1 Jakarta on History Subjects.